Banker's Right to Recover Money Paid by Mistake - Zafrullah, H.M. (Journal of Malaysian and Comparative Law, 2019)
The object of this article is to cover both English and Roman-Dutch law on the subject of the banker's right to recover money paid under a mistake of fact. Restitution in English law is based on a quasi-contractual action also known as an action for money had and received. In Roman Dutch law such payment is recoverable under the action condictio indebiti, a species of the enrichment actions known to that legal system. The origin of the condictio indebiti can be traced back to the classicial period of Roman Law.